Developing heritage trails in Teluk Intan for educational tourism/ Rosnah Mohamad Alias - Mohamad Alias, Rosnah (2017)
Heritage trail is typically categorized as one of the tools in tourism promotion and packaging. The formation of heritage trail normally has given prior attention to tourist demands and needs. Despite the potential of heritage trail for other fields or purposes are rarely explored. This study is significance to the domain of urban design framework, heritage management and tourism packaging, as it gathers and compiles knowledge related to the initial planning and design of heritage trail. The methodology of the study involves the implementation stages of secondary data from government department and existing data from previous researcher that already published. All the data synthesized to identify the potential area to be developed and preserved. Based on the design idea and concept of "Authentic Odyssey in Teluk Intan" that has been transform into physical form in designing the open space to be more functioning, the conservation of the heritage building and the heritage route system to make place more authentic with its own hictorical value. Hopefully, this project can be used as a design strategies and guidelines to develop heritage trail in Teluk Intan.